Investigating Spatial Distribution of Green-Tide in the Yellow Sea in 2021 Using Combined Optical and SAR Images - Yufei Ma; Kapo Wong; Jin Yeu Tsou; Yuanzhi Zhang (Journal of Marine Science and Engineering, 2022)
Optical remote sensing is limited to clouds and rain. It is difficult to obtain ground object images in severe weather. Microwave remote sensing can penetrate clouds and rain to obtain ground object images. Therefore, this paper combines optical and microwave data to analyze the time and space of the green-tide in the Yellow Sea in 2021. Compared with a single data source, the distribution characteristics increase the frequency of time observation and show the green-tide changes in more detail. The continuous remote sensing observation time is 80 days. Ulva prolifera has experienced discovery (mid-late May), development (mid-late May to early June), outbreak (early June to mid-late June), decline (late June to mid-July), and extinction (late July to mid-August) in five stages; the development period drifts along the northeast direction, the outbreak period drifts along the northwest direction, the decline and extinction periods are mainly in the Rizhao and Qingdao waters. Ulva prolifera has a tendency to drift northward as a whole, drifting through Yancheng, Lianyungang, Linyi, Rizhao and Qingdao waters eventually landing on the coast of Qingdao and gradually disappearing.